Modelo de gestión administrativa para los hoteles del cantón Latacunga - Viteri Borja, Paola Nataly (2017)
This research has aimed to determine an administrative management model that contributes to the improvement of the organizational culture for hotels of Latacunga county, this model is based on establishing the steps necessary to achieve efficient administration of both material and economic resources, so the administrative management model proposed by Henry Fayol was designed with the purpose of establishing programs that must be performed within the planning, organization, management and control, which allowed to assign functions to each one of the areas that a hotel counts, such as: administration, finance, production, marketing, and human talent, for the sole purpose of structuring efficiently the structural organization which has a hotel. The research methodology is based on an exploratory unstructured approach study, which was based on small samples and had intended to provide knowledge and understanding of the problem environment, with a descriptive research and theoretical method, this methodology is essential for the development and execution of the project….